Peningkatan Keterampilan Menulis Puisi Bebas dengan Metode Experiential Learning pada Siswa Sekolah Dasar - Gugun Gunadi; Teguh Prasetyo; Daningsih Kurniasari; Iyon Muhdiyati (Universitas Cokroaminoto Palopo, 2023)
The research aims to improve the free poetry writing skills of class III students of MIS Darul Ihya using the Experiential Learning model. The method used in this research is Classroom Action Research (CAR), which consists of two cycles. PTK was conducted to find out how much the experiential learning method can improve class V students' free poetry writing skills. This research was conducted in class III MIS Darul Ihya, Ciomas District, Bogor Regency. The subjects of this study were 29 students of class III MIS Darul Ihya from November 2021 - January 2022. Each intervention cycle included planning, implementing, observing, and reflecting. The planning stage involves preparing teaching materials, research instruments, and observer guides. At the implementation stage, the Experiential Learning model is applied in a structured learning process following the Learning Implementation Plan (RPP), which consists of initial, core, and final activities. The results showed a significant increase in students' poetry writing skills, with an average score increasing in the classical mastery of poetry writing skills before the action. I grew to 70.05 with an excellent category (70% -79%). In cycle II, it increased to 81.05 with a perfect type (80% -89%). These findings indicate that the Experiential Learning model is a practical approach to improving students' poetry writing skills and can be recommended for classroom settings. However, further research is needed to investigate the long-term effects of this approach and its suitability for different groups of students